Tantangan dan Strategi Pemertahanan Bahasa Indonesia pada Siswa Sekolah Dasar Indonesia di Luar Negeri - Ladyanna, Sonezza (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This article describes the challenges and strategies for maintaining the Indonesian language for Indonesian elementary school students who are currently abroad for a non-permanent period. This research was conducted qualitatively. The subject of this research is the challenges and strategies for maintaining the Indonesian language in Indonesian elementary school students who are (schooled) abroad for a non-permanent time. The object of this research is elementary school students of Indonesian citizenship in South Korea. Data were collected using observations and interviews with students and their parents from September 2021-March 2022. Then, the data were analyzed qualitatively descriptively. Based on the results of the study, it was found that the challenges of Indonesian elementary school students living temporarily in South Korea in maintaining language were in the use of the official Indonesian language, both written and spoken. The strategies found in maintaining the Indonesian language include parents teaching Indonesian language using textbooks and teaching materials from pages provided by the Ministry of Education and Culture of the Republic of Indonesia and students taking Indonesian language lessons through direct online courses with subject teachers from Indonesia.